Shoot 'em up [videorecording (DVD)] - Davis, Michael, 1961 August 1-; Owen, Clive; Giamatti, Paul; Bellucci, Monica, 1968-; McHattie, Stephen (New Line Home Entertainment, 2008)
Mr. Smith is not the best idea for looking after a child, yet after stumbling upon a blazing shoot-out, helping to birth a child amidst a hail of gunfire, and seeing the mother die before his eyes, he becomes determined to protect the young innocent at all costs. His adversaries are equally determined, and they will not stop until the newborn is dead. Now, in order to ensure that maniacal criminal mastermind Mr. Hertz and his gang of henchmen do not succeed in accomplishing their evil deeds, Mr. Smith joins forces with a prostitute known as the Dairy Queen, who specializes in lactation fetishes, and flees into the bowels of the city while facing almost certain death on every street corner.